Evaluation of subjective visual vertical and horizontal in patients with acoustic neuroma based on virtual reality - Zhang, Lin; Ouyang, Shunlin; Chen, Ling; Huang, Hemei; Ou, Yongkang; Tang, Xiaowu (Frontiers in Neuroscience, 2023)
Objective: To investigate potential differences in absolute deviation values of subjective visual vertical and horizontal between unilateral acoustic neuroma patients and healthy young adults under varying degrees of static head tilt, as well as the impact of proprioception on these values, with the aim of determining the effect of acoustic neuroma on gravity sensory pathway function in patients.: We recruited 22 patients diagnosed with unilateral acoustic neuroma and 25 healthy young adults and employed virtual reality technology to assess the absolute deviation values of subjective visual vertical (SVV) and subjective visual horizontal (SVH) under eight different static tilted head positions(Head centered (0° tilt), PdP, Head tilt 15°,30° , 45° to the left and right), then compare and analyze intergroup differences.Results: In the Head-centered position, both SVV and SVH absolute deviated values were significantly higher in the AN group compared to healthy young adults. The AN group exhibited significantly higher absolute deviation values of SVV compared to the healthy group when tilting their head 30° left and right. Additionally, when tilting their heads to the right at 15° and 45°, the AN group showed significant increases in SVH absolute deviated values compared to healthy adults. The SVV and SVH absolute deviation values of LAN and SAN groups did not reach statistical significance. The results of the SVV test for PDP position did not show any significant differences among all groups. However, the SVH test revealed that the absolute deviation values of the LAN group was significantly higher than that of healthy individuals.Our study shows that the gravity sensing function of patients with unilateral acoustic neuroma is affected to different degrees, however, the degree of gravity sensing function damage of patients has little relationship with tumor size.When acoustic neuroma is larger than 2 cm, the effect of proprioception on patients' SVH outcome is noteworthy. So, we should pay attention to the postoperative followup of patients with acoustic neuroma and the evaluation of vestibular rehabilitation effect. Meanwhile, for patients opting for conservative treatment, it is imperative to monitor the dynamic changes in vestibular function and seize timely opportunities for intervention.